DESAIN DAN IMPLEMENTASI SISTEM PEMBELAJARAN ELEKTRONIK BERBASIS WEB PADA RUMUS MATEMATIKA DASAR MENGGUNAKAN FRAMEWORK LARAVEL - Evendi - (FKOM UNIKU, 2020)
This research aims to improve the quality of education with the main principles of learning using electronic or computer systems so that they can support learning. Learning methods in the world of education increase rapidly with the existence of information technology. Electronic learning or e-learning is one of the learning methods that emerged due to the development of information technology. The e-learning application will be built using the Laravel Framework. Laravel is chosen because it has a concept of programming based on the Model View Controller (MVC). MVC programming is a programming method by separating data from views and how to process it. This highly developed website creation technology is balanced with the development of the internet so that various media have been online based such as learning media site, currently there are enough learning media sites on the internet, quality material and experienced teaching staff makes us have to pay quite expensive fees. Therefore e-learning learning media with free material is certainly very helpful for people who want to develop their knowledge. This research results an e-learning website for learning media created using the Laravel framework with features such as direct counting.Keywords : E-Learning , Laravel , MVC